Voltage, Throughput, Power, Reliability, and Multicore Scaling. - Xia, Fei; Rafiev, Ashur; Aalsaud, Ali; Al-Hayanni, Mohammed; Davis, James; Levine, Joshua; Mokhov, Andrey; Romanovsky, Alexander; Shafik, Rishad; Yakovlev, Alex; Yang, Sheng (Computer (00189162), 2017)
This article studies the interplay between the performance, energy, and reliability (PER) of parallel-computing systems. It describes methods supporting the meaningful cross-platform analysis of this interplay. These methods lead to the PER software tool, which helps designers analyze, compare, and explore these properties. The web extra at https://youtu.be/aijVMM3Klfc illustrates the PER (performance, energy, and reliability) tool, expanding on the main engineering principles described in the article.